Surveillance the occurrence of black stem rust disease Ug 99 on different wheat cultivars (Triticum aestivum.L) and evaluation of their growth characteristics in the fields of Diyala province, Iraq - Salim, Hussein Ali; Faydh, Abid Hameed; Salman, Mahmood Matrood; Abdulrahman, Abbas Lateef (Journal of Scientific Agriculture, 2017)
Abstract Five wheat cultivars (8/172, 8/70, Tammuz/4, Guard and 124) were planted in the field at the Baladrooz district, Diyala province, Iraq during winter season 2011 to monitor the emergence of Ug 99 on different wheat cultivars and evaluate their performance under similar conditions in the field. The experimental unit consisted of 15 plots in area 25 m2 for each plot according to randomized complete block design. Results showed all cultivars of wheat were not exposure to infection by the black stem rust disease (Ug 99), cultivar of 8/172 gave the highest number of spikes /m2, weight of grains /m2 (g) and weight of grains /25 m2 (g) from another treatments which recorded (401.0, 601.5g and 15037.5 g) respectively. Wheat cultivars of Tammuz/4 and 124 gave the highest total weight of 50 plants which recorded (140 g), whereas Tammuz/4 surpassed other treatments in plant height (79 cm) and 124 cultivar was superior from other treatments in weight of 1000 grains (36.3 g).